"If the mother does not know, there is no way she can tell the adolescent to go for drugs": Challenges in promoting health and preventing transmission among pregnant and parenting Kenyan adolescents living with HIV. (August 2019) - Luseno, Winnie K.; Iritani, Bonita J.; Maman, Suzanne; Mbai, Isabella; Ongili, Barrack; Otieno, Florence Anyango; Hallfors, Denise Dion
Abstract: Adolescents living with HIV (ALHIV) who are pregnant, or parenting, are an important but understudied group. This study explores the challenges in promoting the health of these adolescents and preventing onward transmission. We used existing semi-structured interview data from a 2014 study conducted among Kenyan ALHIV (ages 15–19), their family members, and local health staff to examine adolescent HIV-testing, disclosure, and treatment engagement, focusing on participants who were pregnant, had given birth, or had fathered a child. A total of 28 participant interviews were analyzed, including those conducted with nine ALHIV, four family members, and 15 HIV providers. Four adolescent participants were not in care at the time of their interview. Our analysis also included a transcript from a stakeholder meeting involving HIV providers and associated administrators, held to disseminate and garner feedback on, preliminary findings from the original study. Based on our analysis, adolescents frequently reported being alone during testing, experiencing fear and denial on receiving their results, and delaying disclosure to family and linkage to treatment. They also mentioned a lack of contraceptive counseling, with some reporting multiple pregnancies. Providers voiced misgivings and uncertainty about disclosing HIV diagnoses to minor adolescents without a family member present and reported severe shortages of personnel and resources to adequately serve ALHIV in rural clinics. These findings highlight gaps in services that limit adolescent engagement in HIV treatment prior to sexual debut and conceiving a child, and in PMTCT during and after pregnancy. Greater research attention is needed to address ALHIV reproductive health needs, improve linkage to HIV treatment, and prevent onward sexual transmission. Empirical ethics studies of current adolescent disclosure policies are also warranted to examine cultural and developmental appropriateness, and effectiveness in fostering support and engagement in HIV services. Highlights: Pregnant or parenting Kenyan adolescents often receive their HIV test results alone. Psychosocial reactions and stigma inhibit disclosing one's HIV diagnosis to family. Lack of disclosure and social support undermines utilization of HIV services. Clinics lack resources and contraceptive services for pregnant adolescents with HIV.